P-029 YI The Impact of IBD Patient Demographic Characteristics on Access to Healthcare. (March 2016) - Feld, Lauren; Rodriquez, Dylan; Margolese, Joel; Rosh, Joel; Rubin, Michele; Kim, Sandra; Rubin, David
Abstract : Background: In 2013, the Crohn's and Colitis Foundation of America (CCFA) Health Care Access Task Force performed a national survey using the modified CDC National Health Interview Survey. This survey provided data regarding access to healthcare resources and expert care for patients with inflammatory bowel diseases (IBD) 1 and previously identified a significant number of patients with healthcare-related financial worry who had forgone a variety of medical services due to cost, lack of prompt access to care, and worry over medical coverage. In this analysis, we sought to determine the demographic variables that influence access to care, and specifically, to identify the patients at high risk for insufficient access to care. Methods: This is a subset analysis of the previously described survey, which had been emailed to the entire CCFA mailing list. We reviewed the data from the 3646 U.S. respondents and analyzed patient characteristics associated with reduced healthcare access, including healthcare-related financial worry, insurance status, access to medical therapies, and delays in care. Analysis of data was performed using SPSS Inc. statistical analysis software, utilizing ANOVA, χ 2 tests, binary logistic regression, and independent-sample t -tests. Results: Of the total cohort, one fifth of patients (21.8%, n = 770) were "very worried" about paying medical bills. Patient characteristics that significantly contributed to the variance of worry about medical bills include IBD severity, IBD symptom control, age, gender, insurance type, education, income, marital status, work status and employment (all with P < 0.001). Of the 452 patients (12.5%) who purchased insurance in the past 3 years, 323 patients (71.5%) reported it was "very difficult" to find an insurance plan they could afford, and 270 patients (59%) found it "very difficult" to find the insurance coverage they need. Several demographic variables were significantly associated with difficulties with insurance coverage and affordability ( P < 0.05), including more frequent IBD symptoms, lower income, younger age, and self-identification as disabled or not currently working. Whether or not patients had delayed therapy recently was significantly associated with healthcare-related financial worry, c 2 (4, N = 3528) = 367.14, P < 0.001, with half of patients in the "very worried" group reporting delayed care (49.7%, n = 383), and only 11% (n = 139) of the "not worried" group delaying care. Of the 902 patients (25%) who reported delayed medical care in the past 12 months, half of these individuals (52.4%, n = 848) reported that the delay was due to the cost of care. Those most likely to delay medical care had more severe IBD, reported a flare in the past 12 months, were age 21 to 30 years or 41 to 50 years, had lower income, and had either no insurance, insurance through a spouse's plan, Medicare/Medicaid, or were the primary person on the plan. Patients who delayed getting healthcare were 1.3 times more likely to have reported an IBD flare in the past year (95% CI 1.2–1.4, P < 0.001). Conclusions: We define an at-risk group of IBD patients who have inadequate health care access and associated disability, active IBD symptoms, and delays and deficiencies in their receipt of care. Ongoing and future interventions should target this group of high-risk patients.